Inventory of Meat Rendang Recipes in Nagari Lubuk Gadang, Sangir District, South Solok Regency - Sri Marleni; Asmar Yulastri (Universitas Negeri Padang, 2021)
This study aims to inventory the recipe for beef rendang, identify the ingredients used for making beef rendang, identify the equipment used and explain the process of making beef rendang in Lubuk Gadang village. The type of research used is descriptive research with a qualitative approach method. Data collection techniques by conducting observations, interviews and documentation in the field. After collecting data, the authors got specific research findings, these findings are in accordance with the research objectives, the first is about the ingredients for making beef rendang in the form of: meat, coconut milk, ground chilies, shallots, garlic, coriander, ginger, galangal, cumin, cloves. , cinnamon, mardamunggu, candlenut, palm sugar, turmeric, deaf, turmeric leaves, lime leaves, bay leaves, lemongrass, kandis acid, salt, Mambu and lime. The second finding is in the form of tools used in processing, namely: iron cauldron, iron furnace, stone furnace, iron spoon, millstone. Next about the processing process that starts from the preparation of materials until ready to be served.